Pembuatan Augmented Reality Menggunakan Metode Marker Based Tracking Sebagai Media Edukasi Budidaya Ikan Lele Di Bomo Krajan Banyuwangi - rivaldo aldiansyah; Rachman Yulianto (Sekolah Tinggi Ilmu Komputer PGRI Banyuwangi, 2023)
The lack of information is one of the challenges faced by people who want to start catfish farming in Banyuwangi, due to a lack of knowledge about catfish farming methods. This is what motivates the author to provide information recommendations using Augmented Reality-based technology as an educational medium. The implementation aims to reach people who want to learn how to farm catfish, from selecting fingerlings to the harvesting process. The method used in creating this learning media is the application of AR (Augmented Reality) technology. Augmented Reality can provide easily understandable and absorbable supporting information. This technique also offers an attractive interface by combining various multimedia aspects, including visuals, audio, and text simultaneously. Augmented reality-based video is applied through brochures. Testing on different smartphones resulted in effective marker recognition in lighting conditions of 10 Lux and above, at distances below 20cm. Marker recognition becomes challenging when markers are torn, wet, scribbled, or damaged.